(untitled) (South Asian Journal of Agriculture, 2023)
Bangladesh is a riverine country. There is plenty of surface water, but people cannot use it for all purposes. Most people use groundwater every day for various purposes. A research work was conducted to observe the quality of groundwater of Gournadi upazila of Barishal District for irrigation, drinking, and livestock consumption. Twenty groundwater samples were collected from different locations in Gournadi and the pH, EC, TDS, Ca, Mg, K, Na, S, and P were analyzed in the Department of Agricultural Chemistry, Patuakhali Science and Technology University. The water pH (6.70-8.28) indicated that groundwater samples were neutral to alkaline in nature and they are suitable for irrigation, drinking, and livestock consumption purposes. Based on EC values (0.188- 0.815 mS cm-1), all the samples were found non-saline and suitable for all purposes. The TDS values in groundwater samples collected from Gournadi upazila ranged from 28.8 to 721.6 mgL-1which is under the permissible limit for using in the said purposes. The concentration of Ca, Mg, Na, P, S, and K ions ranged from 3.17-7.67, 2.07-8.77, 6.20-14.65, 0.064-0.80, 3.76-13.81, and 3.34-9.47 mgL-1, respectively. On the basis of Ca, Mg, Na, P, S, and K concentrations all the groundwater samples were rated suitable for irrigation, drinking, and livestock consumption and could be recommended for these purposes. South Asian J. Agric., Vol. 9, No.1&2, 2022-‘23: 72-79